Mine Workers’ Perceptions Of Environmental Accounting (Study on PT Sentral Labuan Tegar Mandiri) - Rina; Sugianto; Ernawaty Usman; Tenripada (GoodWill Journal of Economics, Management, and Accounting, 2025)
This study aims to understand the views of mine workers regarding environmental accounting using a phenomenological approach. The research was conducted at PT Sentral Labuan Tegar Mandiri, a C excavation mining company located in Labuan Main Village, Labuan District, Donggala Regency, Central Sulawesi. This study focuses on three main dimensions in the concept of the Triple Bottom Line, namely environmental, economic, and social aspects. Data collection was carried out through in-depth interviews and direct observations in the field. The findings of the study show that although workers' technical knowledge related to environmental accounting is still limited, they show a high level of concern and awareness of the impact of mining activities, both on the environment and society. The workers understand the importance of waste management, environmental preservation through tree planting, and the role of companies in improving the economic and social conditions of local communities. In general, environmental accounting is understood as a form of corporate commitment to environmental sustainability, social welfare, and regional economic development.